2018
DOI: 10.1002/ptr.6100
|View full text |Cite
|
Sign up to set email alerts
|

Paeonol extracted from Paeonia suffruticosa Andr. ameliorated UVB‐induced skin photoaging via DLD/Nrf2/ARE and MAPK/AP‐1 pathway

Abstract: Paeonia suffruticosa Andr. (PS) has been used in traditional Chinese medicine for a long time. However, there are no studies that investigate the preventive effects of PS on ultraviolet B (UVB)-induced photoaging. In this study, paeonol (PA) was detected the main compound in PS root. In vitro, PS and PA significantly inhibited UVB-induced phosphorylation of mitogen-activated protein kinase and activator protein 1 in keratinocytes, which consequently led to degradation of procollagen type I. On the other hand, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…As an important member in MMPs, MMP‐1 and MMP‐9 co‐degrade collagen, elastin and other structural proteins in ECM , which not only leads to wrinkle formation, sagging skin, but also exacerbate trans epidermal water loss and reduces skin hydration . Type I procollagen is the main structural component of ECM, and MMP‐1 specifically degrades Type I procollagen during photoaging . Loss of structural integrity of ECM is considered to be the main cause of photoinduced skin wrinkling.…”
Section: Introductionmentioning
confidence: 99%
“…As an important member in MMPs, MMP‐1 and MMP‐9 co‐degrade collagen, elastin and other structural proteins in ECM , which not only leads to wrinkle formation, sagging skin, but also exacerbate trans epidermal water loss and reduces skin hydration . Type I procollagen is the main structural component of ECM, and MMP‐1 specifically degrades Type I procollagen during photoaging . Loss of structural integrity of ECM is considered to be the main cause of photoinduced skin wrinkling.…”
Section: Introductionmentioning
confidence: 99%
“…Paeonia suffruticosa is an important Chinese herbal medicine for the treatment of pain and inflammatory disease, including osteoarthritis [6]. Previously, scholars usually focused on its root extracts, such as paeonol or its analogues, as effective pharmaceutical ingredients, but other parts of the herb have not been fully studied [7,8]. Recently, it was found that the seeds of P. suffruticosa are rich in oligostilbenes, including resveratrol and its dimers and trimers [9].…”
Section: Introductionmentioning
confidence: 99%
“…EPI-induced hepatocyte oxidative stress and paeonolrelated antioxidants change a series of biochemical parameters, which impact downstream metabolic processes (6,7). Conventional judgment of hepatotoxicity is principally according to the changes of aminopherases, including aspartate transaminase (AST), which increased after hepatonecrosis (8).…”
Section: Introductionmentioning
confidence: 99%